Uji Ketoksikan Akut Ekstrak Etanol Kangkung darat (Ipomoea reptans Poir) dan air (Ipomoea aquatic Forsk) Menggunakan Metode OECD 423 - Hesti Wulan S, A.Ariani; Putri Sekar Langit, Navtalina (Jurnal Farmasi (Journal of Pharmacy), 2021)
Kangkung have two types, namely Ipomoea reptans Poir and Ipomoea aquatic Forsk. Spinach can be used for herbal terapy including sedative, hypnotic, antidiabetic, analgetic and anxiolytic. Herbal medicine are used for a long time, which is more than a week, so it is necessary to know their safety so that they do not cause unwanted harmful effects. The purpose of this study was to determine the effect of toxicity and to determine the LD50 value of ethanolic extract Ipomoea reptans Poir and Ipomoea aquatic Forsk using the OECD 423 method. This study used mice as test animals, Mus musculus, using a dose of 300 mg/KgBW, followed by a dose of 2000 mg/KgBW. Given orally once during the treatment, physical symptoms such as cyanosis, seizures, respiratory rate for the first 4 hour and the number of deaths were calculated. Observations were continued until day 14. If death occurred in the first 24 hours, it was repeated. The results of py phytochemical screening of ethanol extract Ipomoea reptans Poir and Ipomoea aquatic Forsk were positif for flavonoids, tannins, steroidal, saponins, and vitamins C and E. Based on the results of observations, the number of deaths was then adjusted to GHCS ethanol extract Ipomoea reptans Poir and Ipomoea aquatic Forsk LD50 > 2000-5000 mg/KgBW